A study of clinical spectrum of patterns of cutaneous adverse drug reactions in a tertiary care hospital - Gangaiah, Narendra; Thimmappa, Veena; Gajam, Harish Kumar; Kumar, Naveen (International Journal of Research in Dermatology, 2019)
Background: Adverse drug reactions are unwanted pharmacodynamic effects following administration of a drug. With an increase in number of newer drugs adverse drug reactions have become very common in recent times. Among them cutaneous reactions have been steadily gaining importance and constitute a major proportion of all the adverse drug reactions. Methods: This observational study was conducted at Sri Siddhartha Medical College and Hospital Tumkur, Karnataka, India, involving 73 patients with cutaneous adverse drug reaction (CADR) during November 2016 to May 2018. The aim of the study is to identify the causal drug and categorised into definite/probable/possible Naranjo Algorithm scale was used. Results: The mean age of study participants was 35 years. Majority of cases observed had fixed drug eruptions (FDE: 37%), followed by maculo papular drug reaction (MPDR: 26%). Antimicrobials (42%), non-steroidal anti-inflammatory drugs (NSAIDs: 26%), anticonvulsants (9.5%) were commonly implicated drugs causing CADR. Among those with FDE, definite causality was highest for NSAIDs (9.6%) predominantly paracetamol whereas in MPDR definite causality was noted with anti-tubercular drugs (rifampicin 1.4%) and probable causality was highest for cephalosporins (5.5%) predominantly cefpodoxime. In present study it was observed female patient aged ≥35 years showed statistically significant mucosal involvement and past history of CADRs. Conclusions: A wide range of clinical spectrum of CADRs ranging from FDE to serious toxic epidermal necrolysis was observed. Most of these drug eruptions were caused by antimicrobials. Eliciting past history of CADRs with causal association will help to prevent and manage cases in a better way.